(untitled) (Bangladesh Journal of Pharmacology, 2017)
The effectiveness of water decoction of Tagetes patula was studied against the chronic nonbacterial prostatitis in a rat model induced by estradiol subcuta-neously in a castrated male rat. The low-dose decoction of T. patula significantly ameliorated the prostatitis. The low-dose of polysaccharide and supernatant constituent of T. patula decreased the levels of IL-1?, TNF-?, PSA, and EGF, and improved the levels of testosterone and dihydrotestosterone in vivo. Further, the chemical study indicated that flavonoids were predominant in the supernatant constituent of T. patula. The flavonoids and polysaccha-rides were the effective constituents against prostatitis and this effect may be mediated by keeping hormone balance and a down-regulation of the in?ammatory mediator level of the prostate. Video Clip of Methodology: 9 min 43 Sec Click to watch